On the impact of hepatitis C virus and heterologous immunity on alloimmune responses following liver transplantation. Issue 1 (5th July 2020) - Merritt, Elliot; Londoño, Maria‐Carlota; Childs, Kate; Whitehouse, Gavin; Kodela, Elisavet; Sánchez‐Fueyo, Alberto; Martínez‐Llordella, Marc
Abstract : Virus‐induced heterologous immunity is considered a barrier to transplantation tolerance. Yet, hepatitis C (HCV)‐infected liver transplant (LT) patients occasionally achieve operational tolerance. We investigated the mechanisms through which HCV infection modulates donor‐specific T cell responses following LT and the influence of HCV eradication. We generated T cell lines from HCV‐infected LT and non‐LT patients before and after HCV eradication and quantified alloreactive responses using cell lines expressing single‐HLA class‐I antigens in the presence/absence of PD‐1/CTLA‐4 blockade. HCV‐specific CD8 + T cells cross‐reacted with allogeneic class‐I HLA molecules. HCV‐positive LT recipients exhibited a higher proportion of CD8 + T cells coexpressing inhibitory receptors (PD‐1/CTLA4) than HCV‐negative LT, and their expression correlated with CXCL10 plasma levels. This resulted in decreased antidonor and third‐party proliferative responses, which were significantly reversed by HCV eradication. PD‐1/CTLA‐4 blockade increased the proportion of HCV‐specific CD8 + T cells reacting against donor only before viral clearance. In conclusion, HCV infection results in the generation of HCV‐specific CD8 + T cells capable of reacting against allogeneic HLA molecules. Following LT, this results in a PD‐1/CTLA4‐dependent decrease in alloimmune responses. Our findings challenge the notion that heterologous immunity is necessarily detrimental in LT and provide an explanation for the association between HCV eradication and immune‐mediated allograft damage. Abstract : In liver transplant recipients, hepatitis C–specific CD8+ T cells can crossreact with allogeneic HLA molecules, resulting in a PD‐1/CTLA4‐dependent decrease in alloimmune responses.